Computer Simulation Model of High Efficiency Wireless DC Power Supply - Atiq Aminudin, Muhammad; Baharom, Rahimi; Hashim, Norazlan (International Journal of Engineering and Technology, 2019)
This paper presents the computer simulation model of high efficiency wireless DC power supply. The proposed system uses 20 kHz switching frequency of the half-bridge inverter and this value is suitable for the wireless power transfer in order to obtain high efficiency power transfer. In this work, the mutual inductance is used to present the wireless power transfer (WPT) function. The parameter used is based on the actual practical values of Vishay Radial Wireless Charging Transmitter Coil details. This future innovative technology of WPT system is possible to supply electric power especially for mobile or rotating devices without any wire or cable. The WPT system was targeted to achieve power transfer efficiency of higher than 90% between the transmitter and receiver coils. A computer simulation model using MATLAB/Simulink was developed to investigate the behavior and possible inaccuracies of the proposed system.Â